Desain Rancangan Kemasan Makanan Ringan (Coklat) dengan Metode Theory Of Inventive Problem Solving (TRIZ) di UKM Himasweets Tembung - Silitonga, Putri Elita; Hasibuan, Yetti Meuthia; Utama, Denny Walady (CV. IRA PUBLISHING, 2023)
This research at UKM Himasweet Tembung evaluated snack food (chocolate) packaging that was less attractive and standard, using clear plastic without information on halal logos, composition, or trademarks. The research aims to design more attractive packaging according to consumer desires, using the TRIZ method, which focuses on previous experience and eliminates contradictions. Adequate packaging is essential to protect products, convey information, and increase appeal. A survey method with a questionnaire of 100 respondents was used to collect data. Analysis using TRIZ produces recommendations for packaging improvements. As a result, the ideal snack packaging is a yellow aluminum foil standing pouch with dimensions of 14 x 25 cm (250 gr), yellow brand writing, ziplock, product information, and a picture of the snack (brown) to represent the product.